Gestión del Marketing Mix de servicios en un museo de memoria: Estudio de caso sobre el Lugar de la Memoria, la Tolerancia y la Inclusión Social - Tena Mucha, Esmeralda Marvi (2018)
The present study focuses on knowing how “Lugar de la Memoria, la Tolerancia y la Inclusión Social” (LUM) manages each of the elements of the marketing mix in the first quarter of 2017. At the methodological level, the research had a mixed approach, an exploratory-descriptive scope, gathering information through on-site observations of the museum and interviews with the administrative staff. The analysis was structured according to each of the elements of the marketing mix. The information from the staff interviews showed that the LUM does not have strategies reflected in a marketing plan, although it does carry out activities to reach its target audience. It was identified that several initiatives have delays in their execution due to bureaucratic issues.Likewise, the observations revealed that, for the most part, the LUM complies with the established benchmarks. Finally, recommendations are proposed to improve the management of the marketing mix: the definition of a plan that specifies marketing strategies and tactics related to the different Ps, including those linked to the optimization of internal and external signage, the improvement of the descriptions of the exhibition, and the diversification of additional activities, among others.